2016
DOI: 10.1002/bjs.10304
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of neoadjuvant therapies for cancer of the oesophagus or gastro-oesophageal junction based on a national data registry

Abstract: For patients with squamous cell carcinoma of the oesophagus or gastro-oesophageal junction, neoadjuvant treatments seemed to increase long-term survival, but also the risk of postoperative morbidity and mortality, compared with surgery alone. Neither neoadjuvant treatment option seemed to improve survival significantly among patients with adenocarcinoma, compared with surgery alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
2
19
0
2
Order By: Relevance
“…Most previous studies revealed nCRT was not associated with improved survival in spite of its apparent elevated pCR rate compared with nCT (3,20,21,25). It was worth mentioning that nCRT group carried an increased risk of postoperative mortality or had more deaths unrelated to disease progression in the first-year follow up period in these studies.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…Most previous studies revealed nCRT was not associated with improved survival in spite of its apparent elevated pCR rate compared with nCT (3,20,21,25). It was worth mentioning that nCRT group carried an increased risk of postoperative mortality or had more deaths unrelated to disease progression in the first-year follow up period in these studies.…”
Section: Discussionmentioning
confidence: 69%
“…In other trials, lymph node retrieval after nCRT also appeared to be lower (1,20,27). Besides, it was reported that chemoradiotherapy reduced lymph node harvest from within the radiotherapy field in rectal cancer (28,29).Most previous studies revealed nCRT was not associated with improved survival in spite of its apparent elevated pCR rate compared with nCT (3,20,21,25). It was worth mentioning that nCRT group carried an increased risk of postoperative mortality or had more deaths unrelated to disease progression in the first-year follow up period in these studies.…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…In the oesophageal cancer group, 25% of the elderly patients received neoadjuvant therapy. Several studies show that neoadjuvant and combined chemoradiotherapy in patients with oesophageal and gastro‐oesophageal junction cancers tend to increase post‐operative morbidity, especially in patients with significant co‐morbid diseases or advanced age . The effect of neoadjuvant chemotherapy alone is more ambiguous, with some studies not showing any negative effects, while others report increased morbidity …”
Section: Discussionmentioning
confidence: 99%